Snap-Back Testing for Estimation of Nonlinear Behaviour of Shallow and Pile Foundations - M.J., Pender; T.B, Algie; N.M, Sa’don; R.P, Orense (Universiti Malaysia Sarawak, UNIMAS, 2011)
We are working on the development of methods for analysing the earthquake response of foundations that make use of Soil-Foundation-Structure- Interaction (SFSI) as a means of incorporating nonlinear soil deformation effects and nonlinear geometrical effects into the earthquake resistant design of foundations. There are three challenges in this work. First, to incorporate adequately the nonlinear response of the soil during the earthquake. Second, to account for geometrical nonlinearity during the earthquake - that is loss of contact between various parts of the foundation and the underlying and/or adjacent soil. Third, to obtain appropriate values for the soil parameters which describe the nonlinear response of the foundations. The main thrust of this paper is to show how snap-back testing is a most effective means of evaluating nonlinear soil behaviour. We consider that snap-back testing is more convenient than using a shaking machine which applies sinusoidal excitation. The results from rocking of a shallow foundation and cyclic lateral loading of a single pile enable damping and stiffness to be estimated at increasing levels of lateral loading.